Neurolinguistic programming in the written vocabulary in senior students of Mariano Suarez Veintimilla School - Portilla Erazo, Jazmín Isamar (2024)
Analyze the influence of neurolinguistic programming in the written vocabulary in senior students at Mariano Suarez Veintimilla School.